The handbook of English linguistics - Hinrichs, Lars; McMahon, April M. S.; Aarts, Bas 1961- (Hoboken, New Jersey John Wiley & Sons Ltd., 2020)
The second edition of the popular Handbook of English Linguistics brings together stimulating discussions of the core topics in English linguistics in a single, authoritative volume. Written by an international team of experts, the chapters cover syntax, methodology, phonetics and phonology, lexis and morphology, variation, stylistics, and discourse, and also provide discussions of theoretical and descriptive research in the field.

The revised edition includes new and updated chapters on English Corpus Linguistics, experimental approaches, complements and adjuncts, English phonology and morphology, lexicography, and more. In-depth yet accessible chapters introduce key areas of English linguistics, discuss relevant research, and suggest future research directions.

An important academic contribution to the field, this book:

• Presents thirty-two in-depth, yet accessible, chapters that discuss new research findings across the field, written by both established and emerging scholars from around the world
• Builds upon the very successful first edition, published in 2006
• Incorporates new trends in English linguistics, including digital research methods and theoretical advances in all subfields
• Suggests future research directions

The Handbook of English Linguistics, 2nd Edition is an essential reference work for researchers and students working in the field of English language and linguistics.
Includes index (pages 637-652).
Keywords: English language -- Handbooks, manuals, etc; Linguistics -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc